Disruptive Effect of Organotin on Thyroid Gland Function Might Contribute to Hypothyroidism - Miriane de Oliveira; Bruna Moretto Rodrigues; Regiane Marques Castro Olimpio; Jones Bernardes Graceli; Bianca Mariani Gonçalves; Sarah Maria Barneze Costa; Tabata Marinda da Silva; Maria Teresa De Sibio; Fernanda Cristina Fontes Moretto; Lucas Solla Mathias; Dariane Beatriz Marino Cardoso; Helena Paim Tilli; et al. (International Journal of Endocrinology)
A considerable increase in endocrine abnormalities has been reported over the last few decades worldwide. A growing exposure to endocrine-disrupting chemicals (EDCs) can be one of the causes of endocrine disorders in populations, and these disorders are not only restricted to the metabolic hormone system but can also cause abnormal functions. Thyroid hormone (TH) disruption is defined as an abnormal change in TH production, transport, function, or metabolism, which results in some degree of impairment in body homeostasis. Many EDCs, including organotin compounds (OTCs), are environmental contaminants that are commonly found in antifouling paints used on ships and in several other industrial procedures. OTCs are obesogenic and can disrupt TH metabolism; however, abnormalities in thyroid function resulting from OTC exposure are less well understood. OTCs, one of the most prevalent EDCs that are encountered on a daily basis, modulate the thyroid axis. In most toxicology studies, it has been reported that OTCs might contribute to hypothyroidism.